Nitrogen-saturated AlNbTiZrN wear-resistant coating with high hardness and preparation method of nitrogen-saturated AlNbTiZrN wear-resistant coating
Through the magnetron sputtering technology of nitrogen-saturated AlNbTiZrN high-entropy alloy coating, the problem of insufficient hardness and wear resistance of traditional coatings under complex working conditions is solved, and a coating with high hardness and wear resistance is achieved, extending the service life of parts and reducing maintenance costs.
Patent Information
- Application Number
- CN202411840693.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-13
AI Technical Summary
Traditional coatings have problems such as insufficient hardness, poor wear resistance and insufficient corrosion resistance under complex working conditions such as high temperature, high pressure, friction, and corrosion, resulting in shortening of the service life of parts and increasing maintenance costs.
A nitrogen-saturated AlNbTiZrN high-entropy alloy coating is used to deposit under low temperature conditions through magnetron sputtering technology, and the nitrogen flow rate is controlled to reach the nitrogen saturation state, forming an FCC structural coating with high hardness and high wear resistance.
It achieves high hardness and wear resistance, improves the mechanical properties and wear resistance of the coating, extends the service life of the parts, and reduces maintenance costs.
Smart Images

Figure CN119710541A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of high entropy alloy coatings and preparation thereof, and particularly relates to a nitrogen-saturated AlNbTiZrN high entropy alloy coating with good mechanical properties and wear resistance and a preparation method thereof. Background Art
[0002] With the extensive application of mechanical devices in traditional manual industries and new scientific and technological fields, the service conditions of key components such as rolling bearings have become increasingly complex. When facing harsh working conditions coupled with multiple factors such as high speed and heavy load, surface failure of key components such as rolling bearings has become a key factor restricting the development of mechanical devices. The service life of key components without surface coating protection is greatly shortened, so the mechanical and tribological properties of the surface protective coating of key components have an important influence on the working performance and service life of key components.
[0003] With the further development of automation in various industries, various surface strengthening technologies have developed rapidly. Traditional coating technologies such as electroplating that are unfavorable to the environment have gradually been eliminated as people's requirements for coating performance and environmental protection continue to increase. However, magnetron sputtering coatings have been widely used in recent years due to their high controllability, low deposition temperature, wide range of plating substrate materials, good mechanical properties and excellent tribological properties.
[0004] Traditional single metal or alloy coatings are difficult to meet the increasingly stringent use requirements in many cases. For example, in the mechanical processing, aerospace, petrochemical and other industries, the surface of parts is often affected by various factors such as high temperature, high pressure, friction, corrosion, etc. Traditional coatings may have problems such as insufficient hardness, poor wear resistance, and insufficient corrosion resistance, which shortens the service life of parts and increases maintenance costs and production risks.
[0005] With the in-depth study of the properties of coating materials, people have found that high entropy alloy coatings have unique structures and excellent properties, and have great application potential in the field of coatings. Summary of the invention
[0006] The present invention aims to solve the problems of traditional coatings such as insufficient hardness, poor wear resistance, insufficient corrosion resistance, etc., and to provide a high entropy alloy coating with good mechanical and tribological properties and a preparation method thereof.
[0007] The nitrogen-saturated AlNbTiZrN wear-resistant coating with high hardness is formed by magnetron sputtering deposition of an AlNbTiZr target material. The nitrogen-saturated AlNbTiZrN wear-resistant coating consists of Al, Nb, Ti, Zr and N elements, and the atomic percentage content of each element is: Al: 18.00at%-34.00at%, Nb: 12.00at%-27.00at%, Ti: 10.90at%-13.48at%, Zr: 10.94at%-25.52at%, and N: 32.16at%-48.16at%.
[0008] The content of N element in the nitrogen-saturated AlNbTiZrN wear-resistant coating of the present invention is optimized to be 44.33 at. % to 48.16 at. %, and the sum of the atomic percentage contents of Al, Nb, Ti, Zr and N elements is 100%.
[0009] The preparation method of the nitrogen-saturated AlNbTiZrN wear-resistant coating with high hardness of the present invention is achieved by the following steps:
[0010] S1. Substrate processing:
[0011] The substrate is ultrasonically cleaned by using ethanol or acetone, and dried to obtain a cleaned substrate;
[0012] S2. Film loading:
[0013] The cleaned substrate is mounted on a rotating fixture, sent into a vacuum chamber of a magnetron sputtering device, and evacuated;
[0014] S3, heating:
[0015] Heat the vacuum chamber to 200-205°C and evacuate the chamber again;
[0016] S4. Substrate cleaning:
[0017] Argon gas is introduced into the vacuum chamber to perform plasma cleaning on the substrate;
[0018] S5. Coating pre-deposition:
[0019] Using AlNbTiZr alloy as the target material, increase the argon flow rate to 100-140 sccm, control the deposition gas pressure to 0.8-1.5 Pa, set the voltage of the bias power supply to 100-200 V, turn on the bias power supply, then turn on the DC pulse power supply, and perform pre-deposition for 2-5 minutes;
[0020] S6. Coating deposition:
[0021] After the pre-deposition is completed, the DC pulse power supply is kept on, the argon flow rate is gradually reduced, the nitrogen flow rate is increased, the argon flow rate is controlled to be 110-120 sccm, the nitrogen flow rate is controlled to be 3-6 sccm, the deposition pressure is maintained at 0.8-1.5 Pa, and vapor deposition is performed;
[0022] S7. Cooling: After the temperature of the vacuum chamber is gradually cooled to room temperature and the atmosphere is vented, the substrate is taken out and a nitrogen-saturated AlNbTiZrN wear-resistant coating with high hardness is deposited on the substrate.
[0023] In the preparation method of the nitrogen-saturated AlNbTiZrN wear-resistant coating with high hardness of the present invention, during the coating deposition process, it is necessary to control the flow rate of nitrogen so that the AlNbTiZr coating reaches a nitrogen (over) saturated state. The Al, Nb, Ti and Zr elements in the AlNbTiZrN wear-resistant coating of the present invention have a high affinity with the nitrogen element, and a high nitrogen content in the coating under a low nitrogen atmosphere is achieved. The high nitrogen content causes the lattice atoms inside the coating to deviate from the equilibrium position, that is, lattice distortion occurs, thereby increasing local internal stress, inhibiting the dislocation movement inside the coating, and the reduction of the average grain size simultaneously causes the internal organization of the film to be denser, thereby increasing the hardness. The wear resistance of the coating is affected by the hardness, elastic deformation and plastic deformation resistance of the coating. The high nitrogen content makes the coating have higher hardness and fracture toughness, so that the coating has better wear resistance. In addition, the oxides and oxide films generated during the friction process can play a certain lubricating role, thereby reducing friction and wear, and improving the mechanical properties and wear resistance of the high entropy alloy coating.
[0024] The nitrogen-saturated AlNbTiZrN wear-resistant coating with high hardness and the preparation method thereof of the present invention have the following beneficial effects:
[0025] 1. The present invention provides an AlNbTiZrN high entropy alloy coating with good mechanical properties and wear resistance. The high entropy alloy coating is mainly composed of an FCC solid solution phase, has a uniform alloy structure, and has broad application prospects in the field of high-temperature alloy coatings.
[0026] 2. Adding nitrogen (N) element to the alloy coating to form a nitride solid solution with FCC structure is beneficial to improve the hardness of the coating.
[0027] 3. The four metal elements of the alloy coating: aluminum (Al), niobium (Nb), titanium (Ti), and zirconium (Zr) can generate four oxides, TiO2, Nb2O5, Al2O3, and ZrO2, during the friction process, which is beneficial to reduce friction.
[0028] 4. The alloy coating is characterized by a high nitrogen content. When the nitrogen flow rate is 12 sccm, the nitrogen content reaches saturation, and as the nitrogen content further increases, the nitrogen content tends to stabilize and reaches a nitrogen saturation state. This is conducive to improving the hardness and modulus of the AlNbTiZrN coating. The hardness of the AlNbTiZrN high entropy alloy coating prepared by the present invention is 9 to 33 GPa, and the elastic modulus is 145 to 469 GPa.
[0029] 5. The AlNbTiZrN high entropy alloy coating prepared by the present invention can improve the bonding strength and overall strength of the coating and the substrate, so that the PVD coating exhibits superior mechanical properties and good wear resistance. The friction coefficient of the AlNbTiZrN high entropy alloy coating prepared by the present invention is 0.55-0.72, and the wear rate is 8.95×10 -8 ~7.78×10 -7 mm 3 ·N -1 mm -1 . BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 X-ray diffraction (XRD) spectra of high entropy alloy coatings prepared in Examples 1 to 3;
[0031] Figure 2 The hardness and modulus bar graphs of the high entropy alloy coatings prepared in Examples 1 to 4;
[0032] Figure 3 The surface scanning electron microscope images of the high entropy alloy coatings prepared in Examples 1 to 4;
[0033] Figure 4 The surface roughness of the high entropy alloy coatings prepared in Examples 1 to 4, wherein (a) represents Example 1, (b) represents Example 2, (c) represents Example 3, and (d) represents Example 4;
[0034] Figure 5 The friction coefficient and wear rate diagram of the high entropy alloy coating prepared in Examples 1 to 3;
[0035] Figure 6 Element content diagram of high entropy alloy coatings prepared in Examples 1 to 4;
[0036] Figure 7 This is an electron microscope image of the high entropy alloy coating prepared in Example 1. DETAILED DESCRIPTION
[0037] Specific implementation method 1: The preparation method of the nitrogen-saturated AlNbTiZrN wear-resistant coating with high hardness in this implementation method is implemented according to the following steps:
[0038] S1. Substrate processing:
[0039] The substrate is ultrasonically cleaned by using ethanol or acetone, and dried to obtain a cleaned substrate;
[0040] S2. Film loading:
[0041] The cleaned substrate is mounted on a rotating fixture, sent into a vacuum chamber of a magnetron sputtering device, and evacuated;
[0042] S3, heating:
[0043] Heat the vacuum chamber to 200-205°C and evacuate the chamber again;
[0044] S4. Substrate cleaning:
[0045] Argon gas is introduced into the vacuum chamber to perform plasma cleaning on the substrate;
[0046] S5. Coating pre-deposition:
[0047] Using AlNbTiZr alloy as the target material, increase the argon flow rate to 100-140 sccm, control the deposition gas pressure to 0.8-1.5 Pa, set the voltage of the bias power supply to 100-200 V, turn on the bias power supply, then turn on the DC pulse power supply, and perform pre-deposition for 2-5 minutes;
[0048] S6. Coating deposition:
[0049] After the pre-deposition is completed, the DC pulse power supply is kept on, the argon flow rate is gradually reduced, the nitrogen flow rate is increased, the argon flow rate is controlled to be 110-120 sccm, the nitrogen flow rate is controlled to be 3-6 sccm, the deposition pressure is maintained at 0.8-1.5 Pa, and vapor deposition is performed;
[0050] S7. Cooling: After the temperature of the vacuum chamber is gradually cooled to room temperature and the atmosphere is vented, the substrate is taken out and a nitrogen-saturated AlNbTiZrN wear-resistant coating with high hardness is deposited on the substrate.
[0051] The surface roughness of the AlNbTiZrN high entropy alloy coating prepared in this embodiment is 0.96-7.91 nm.
[0052] The AlNbTiZrN high entropy alloy coating prepared in this embodiment has an FCC face-centered cubic phase structure, good hardness and wear resistance, and has considerable research value and application potential in the field of high entropy alloy coatings.
[0053] The AlNbTiZrN high entropy alloy coating prepared in this embodiment has reasonable composition, high degree of alloying, good mechanical properties and wear resistance, and meets the requirements for surface protection of materials of extreme environment components such as cutting tools, bearings, gears, and drill bits.
[0054] Specific implementation method 2: The difference between this implementation method and specific implementation method 1 is that the material of the substrate in step S1 is a single metal, ceramic or alloy material.
[0055] Specific implementation method three: This implementation method is different from specific implementation methods one or two in that the time of ultrasonic cleaning in step S1 is 20 to 30 minutes.
[0056] Specific embodiment 4: This embodiment is different from the specific embodiments 1 to 3 in that the vacuum is again pumped to 3×10 -3 Pa.
[0057] Specific embodiment 5: This embodiment is different from specific embodiments 1 to 4 in that the plasma cleaning process in step S4 is as follows:
[0058] Introduce argon gas into the vacuum chamber and control the argon gas flow rate to 17 sccm. First turn on the ion source power supply and use the ion source to clean the substrate surface for 10 to 20 minutes. Then turn off the ion source power supply, turn on the bias power supply, and use the bias to clean for 10 to 20 minutes.
[0059] Specific implementation method 6: This implementation method is different from specific implementation method 5 in that the ion source power supply parameters are set as follows: current is 0.3A, and duty cycle is 70%.
[0060] Specific implementation method seven: This implementation method is different from specific implementation method five in that the bias power supply parameters are set as follows: voltage is 800V, and duty cycle is 50%.
[0061] Specific implementation eight: The difference between this implementation and any one of specific implementations one to seven is that in step S5, the DC pulse power supply parameters are controlled as follows: power is 800-1200W, and duty cycle is 70%.
[0062] Specific implementation method 9: The difference between this implementation method and any one of specific implementation methods 1 to 8 is that in step S6, the argon flow rate is controlled to be 100-105 sccm, the nitrogen flow rate is controlled to be 15-20 sccm, and the deposition pressure is maintained at 1.0 Pa to perform vapor deposition.
[0063] This embodiment optimizes the content of argon and nitrogen during the vapor deposition process, so that the wear resistance of the nitrogen-saturated AlNbTiZrN wear-resistant coating is optimized.
[0064] Specific embodiment ten: This embodiment is different from any one of specific embodiments one to nine in that the thickness of the nitrogen-saturated AlNbTiZrN wear-resistant coating with high hardness in step S7 is 2.5-6.0 μm.
[0065] Embodiment 1: The preparation method of the nitrogen-saturated AlNbTiZrN wear-resistant coating with high hardness in this embodiment is implemented according to the following steps:
[0066] S1. Substrate processing:
[0067] The substrate was ultrasonically cleaned with ethanol for 20 minutes and dried to obtain a cleaned substrate. The substrate was made of 316 stainless steel and had a size of 30 mm×20 mm×2 mm.
[0068] S2. Film loading:
[0069] The cleaned substrate was placed on a rotary fixture and sent into the vacuum chamber of the magnetron sputtering device. The vacuum was evacuated to 5×10 -3 Pa;
[0070] S3, heating:
[0071] Heat the vacuum chamber to 200°C and evacuate the chamber to 3×10 -3 Pa;
[0072] S4. Substrate cleaning:
[0073] Introduce argon gas into the vacuum chamber, control the argon gas flow rate to 17 sccm, first turn on the ion source power supply, use the ion source to clean the substrate surface for 15 minutes, then turn off the ion source power supply, turn on the bias power supply, use the bias to clean for 15 minutes, turn off the bias power supply, and perform plasma cleaning on the substrate;
[0074] S5. Coating pre-deposition:
[0075] Using AlNbTiZr alloy as the target material, increase the argon flow rate to 120 sccm, control the deposition gas pressure to 1.0 Pa, set the voltage of the bias power supply to 100 V, turn on the bias power supply, and then turn on the DC pulse power supply for pre-deposition for 3 minutes;
[0076] S6. Coating deposition:
[0077] After the pre-deposition is completed, keep the DC pulse power supply and the bias power supply turned on, gradually reduce the argon flow rate, increase the nitrogen flow rate, control the argon flow rate to 116sccm, control the nitrogen flow rate to 4sccm, maintain the deposition pressure at 1.0Pa, and perform vapor deposition for 90min;
[0078] S7. Cooling: After the temperature of the vacuum chamber is gradually cooled to room temperature and the atmosphere is vented, the substrate is taken out and a nitrogen-saturated AlNbTiZrN wear-resistant coating with high hardness is deposited on the substrate.
[0079] In step S4 of this embodiment, the ion source power supply parameters are set to: current 0.3A, duty cycle 70%; the bias power supply parameters are set to: voltage 800V, duty cycle 50%. In step S5, the DC pulse power supply parameters are set to: power 1000W, duty cycle 70%.
[0080] The purity of the argon gas used in this embodiment is 99.99%, and the purity of the nitrogen gas is 99.99%.
[0081] The AlNbTiZrN high entropy alloy coating prepared in this embodiment has an XRD spectrum as shown in FIG. Figure 1 As shown, it can be seen that the high entropy alloy composition has an FCC phase structure.
[0082] The hardness curve of the AlNbTiZrN high entropy alloy coating is as follows: Figure 2 As shown, it can be seen that the hardness of the AlNbTiZrN high entropy alloy coating reaches 32.95 GPa and the modulus reaches 468.67 GPa.
[0083] The surface scanning electron microscope image of the AlNbTiZrN high entropy alloy coating is as follows: Figure 3 As shown, the surface quality is good without cracking and peeling.
[0084] The AlNbTiZrN high entropy alloy coating has a surface roughness as follows Figure 4 As shown, its surface roughness is only 4.35nm.
[0085] The friction coefficient and wear rate of the AlNbTiZrN high entropy alloy coating are as follows: Figure 5 As shown in Figure 2, its friction coefficient is 0.6 and the wear rate is only 9.27×10 -8 mm 3 ·N -1 mm -1 .
[0086] The AlNbTiZrN high entropy alloy coating has various element contents as follows: Figure 6 As shown, its nitrogen content is 44.33 at.%.
[0087] Embodiment 2: The preparation method of the nitrogen-saturated AlNbTiZrN wear-resistant coating with high hardness in this embodiment is implemented according to the following steps:
[0088] S1. Substrate processing:
[0089] The substrate was ultrasonically cleaned with ethanol for 20 minutes and dried to obtain a cleaned substrate. The substrate was made of 316 stainless steel and had a size of 30 mm×20 mm×2 mm.
[0090] S2. Film loading:
[0091] The cleaned substrate was placed on a rotary fixture and sent into the vacuum chamber of the magnetron sputtering device. The vacuum was evacuated to 5×10 -3 Pa;
[0092] S3, heating:
[0093] Heat the vacuum chamber to 200°C and evacuate the chamber to 3×10 -3 Pa;
[0094] S4. Substrate cleaning:
[0095] Introduce argon gas into the vacuum chamber, control the argon gas flow rate to 17 sccm, first turn on the ion source power supply, use the ion source to clean the substrate surface for 15 minutes, then turn off the ion source power supply, turn on the bias power supply, use the bias to clean for 15 minutes, turn off the bias power supply, and perform plasma cleaning on the substrate;
[0096] S5. Coating pre-deposition:
[0097] Using AlNbTiZr alloy as the target material, increase the argon flow rate to 120 sccm, control the deposition gas pressure to 1.0 Pa, set the voltage of the bias power supply to 100 V, turn on the bias power supply, and then turn on the DC pulse power supply for pre-deposition for 3 minutes;
[0098] S6. Coating deposition:
[0099] After the pre-deposition is completed, keep the DC pulse power supply and the bias power supply turned on, gradually reduce the argon flow rate, increase the nitrogen flow rate, control the argon flow rate to 100 sccm, control the nitrogen flow rate to 20 sccm, maintain the deposition pressure at 1.0 Pa, and perform vapor deposition for 90 minutes;
[0100] S7. Cooling: After the temperature of the vacuum chamber is gradually cooled to room temperature and the atmosphere is vented, the substrate is taken out and a nitrogen-saturated AlNbTiZrN wear-resistant coating with high hardness is deposited on the substrate.
[0101] In step S4 of this embodiment, the ion source power supply parameters are set to: current 0.3A, duty cycle 70%; the bias power supply parameters are set to: voltage 800V, duty cycle 50%. In step S5, the DC pulse power supply parameters are set to: power 1000W, duty cycle 70%.
[0102] The AlNbTiZrN high entropy alloy coating prepared in this embodiment has an XRD spectrum as shown in FIG. Figure 1 As shown, it can be seen that the high entropy alloy composition has an FCC phase structure.
[0103] The hardness curve of the AlNbTiZrN high entropy alloy coating is as follows: Figure 2As shown, it can be seen that the hardness of the AlNbTiZrN high entropy alloy coating reaches 28.92 GPa and the modulus reaches 359.14 GPa.
[0104] The surface scanning electron microscope image of the AlNbTiZrN high entropy alloy coating is as follows: Figure 3 As shown, the surface quality is good without cracking and peeling.
[0105] The AlNbTiZrN high entropy alloy coating has a surface roughness as follows Figure 4 As shown, its surface roughness is only 3.26nm.
[0106] The friction coefficient and wear rate of the AlNbTiZrN high entropy alloy coating are as follows: Figure 5 As shown in Figure 2, its friction coefficient is 0.5 and the wear rate is only 8.95×10 -8 mm 3 ·N -1 mm -1 The AlNbTiZrN high entropy alloy coating obtained in this embodiment has the best mechanical properties and wear resistance.
[0107] The AlNbTiZrN high entropy alloy coating has various element contents as follows: Figure 6 As shown, its nitrogen content is 46.47 at.%.
[0108] Embodiment 3: The preparation method of the nitrogen-saturated AlNbTiZrN wear-resistant coating with high hardness in this embodiment is implemented according to the following steps:
[0109] S1. Substrate processing:
[0110] The substrate was ultrasonically cleaned with ethanol for 20 minutes and dried to obtain a cleaned substrate. The substrate was made of 316 stainless steel and had a size of 30 mm×20 mm×2 mm.
[0111] S2. Film loading:
[0112] The cleaned substrate was placed on a rotary fixture and sent into the vacuum chamber of the magnetron sputtering device. The vacuum was evacuated to 5×10 -3 Pa;
[0113] S3, heating:
[0114] Heat the vacuum chamber to 200°C and evacuate the chamber to 3×10 -3 Pa;
[0115] S4. Substrate cleaning:
[0116] Introduce argon gas into the vacuum chamber, control the argon gas flow rate to 17 sccm, first turn on the ion source power supply, use the ion source to clean the substrate surface for 15 minutes, then turn off the ion source power supply, turn on the bias power supply, use the bias to clean for 15 minutes, turn off the bias power supply, and perform plasma cleaning on the substrate;
[0117] S5. Coating pre-deposition:
[0118] Using AlNbTiZr alloy as the target material, increase the argon flow rate to 120 sccm, control the deposition gas pressure to 1.0 Pa, set the voltage of the bias power supply to 100 V, turn on the bias power supply, and then turn on the DC pulse power supply for pre-deposition for 3 minutes;
[0119] S6. Coating deposition:
[0120] After the pre-deposition is completed, keep the DC pulse power supply and the bias power supply turned on, gradually reduce the argon flow rate, increase the nitrogen flow rate, control the argon flow rate to 108sccm, control the nitrogen flow rate to 12sccm, maintain the deposition pressure at 1.0Pa, and perform vapor deposition for 90min;
[0121] S7. Cooling: After the temperature of the vacuum chamber is gradually cooled to room temperature and the atmosphere is vented, the substrate is taken out and a nitrogen-saturated AlNbTiZrN wear-resistant coating with high hardness is deposited on the substrate.
[0122] In step S4 of this embodiment, the ion source power supply parameters are set as follows: current: 0.3A, duty cycle: 70%; the bias power supply parameters are set as follows: voltage: 800V, duty cycle: 50%. In step S5, the DC pulse power supply parameters are set as follows: power: 1000W, duty cycle: 70%.
[0123] The AlNbTiZrN high entropy alloy coating prepared in this embodiment has an XRD spectrum as shown in FIG. Figure 1 As shown, it can be seen that the high entropy alloy composition has an FCC phase structure.
[0124] The hardness curve of the AlNbTiZrN high entropy alloy coating is as follows: Figure 2 As shown, it can be seen that the hardness of the AlNbTiZrN high entropy alloy coating reaches 29.38 GPa and the modulus reaches 378.89 GPa.
[0125] The surface scanning electron microscope image of the AlNbTiZrN high entropy alloy coating is as follows: Figure 3 As shown, the surface quality is good without cracking and peeling.
[0126] The AlNbTiZrN high entropy alloy coating has a surface roughness as follows Figure 4 As shown, its surface roughness is only 3.45nm.
[0127] The friction coefficient and wear rate of the AlNbTiZrN high entropy alloy coating are as follows: Figure 5 As shown in Figure 2, its friction coefficient is 0.6 and the wear rate is only 9.75×10 -8 mm 3 ·N -1 mm -1 .
[0128] The AlNbTiZrN high entropy alloy coating has various element contents as follows: Figure 6 As shown, its nitrogen content is 47.44 at.%.
[0129] Comparative Example: The preparation method of the nitrogen-saturated AlNbTiZrN wear-resistant coating with high hardness in this embodiment is implemented according to the following steps:
[0130] S1. Substrate processing:
[0131] The substrate was ultrasonically cleaned with ethanol for 20 minutes and dried to obtain a cleaned substrate. The substrate was made of 316 stainless steel and had a size of 30 mm×20 mm×2 mm.
[0132] S2. Film loading:
[0133] The cleaned substrate was placed on a rotary fixture and sent into the vacuum chamber of the magnetron sputtering device. The vacuum was evacuated to 5×10 -3 Pa;
[0134] S3, heating:
[0135] Heat the vacuum chamber to 200°C and evacuate the chamber to 3×10 -3 Pa;
[0136] S4. Substrate cleaning:
[0137] Introduce argon gas into the vacuum chamber, control the argon gas flow rate to 17 sccm, first turn on the ion source power supply, use the ion source to clean the substrate surface for 15 minutes, then turn off the ion source power supply, turn on the bias power supply, use the bias to clean for 15 minutes, turn off the bias power supply, and perform plasma cleaning on the substrate;
[0138] S5. Coating pre-deposition:
[0139] Using AlNbTiZr alloy as the target material, increase the argon flow rate to 120 sccm, control the deposition gas pressure to 1.0 Pa, set the voltage of the bias power supply to 100 V, turn on the bias power supply, and then turn on the DC pulse power supply for pre-deposition for 3 minutes;
[0140] S6. Coating deposition:
[0141] After the pre-deposition is completed, keep the DC pulse power supply and the bias power supply turned on, gradually reduce the argon flow rate, increase the nitrogen flow rate, control the argon flow rate to 120sccm, control the nitrogen flow rate to 0sccm, maintain the deposition pressure at 1.0Pa, and perform vapor deposition for 90min;
[0142] S7. Cooling: After the temperature of the vacuum chamber is gradually cooled to room temperature and the atmosphere is vented, the substrate is taken out and a nitrogen-saturated AlNbTiZrN wear-resistant coating with high hardness is deposited on the substrate.
[0143] In step S4 of this embodiment, the ion source power supply parameters are set as follows: current: 0.3A, duty cycle: 70%; the bias power supply parameters are set as follows: voltage: 800V, duty cycle: 50%. In step S5, the DC pulse power supply parameters are set as follows: power: 1000W, duty cycle: 70%.
[0144] The hardness curve of the AlNbTiZrN high entropy alloy coating prepared in this embodiment is as follows: Figure 2 As shown, it can be seen that the hardness of the AlNbTiZrN high entropy alloy coating reaches 9.61 GPa and the modulus reaches 145.53 GPa.
[0145] The surface scanning electron microscope image of the AlNbTiZrN high entropy alloy coating is as follows: Figure 3 As shown, the surface quality is good without cracking and peeling.
[0146] The AlNbTiZrN high entropy alloy coating has a surface roughness as follows Figure 4 As shown, its surface roughness is only 0.96nm.
[0147] The friction coefficient and wear rate of the AlNbTiZrN high entropy alloy coating are as follows: Figure 5 As shown in Figure 2, its friction coefficient is 0.7 and the wear rate is only 7.78×10 -7 mm 3 ·N -1 mm -1 .
[0148] The AlNbTiZrN high entropy alloy coating has various element contents as follows: Figure 6 As shown, its nitrogen content is 0.
[0149] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A nitrogen-saturated AlNbTiZrN wear-resistant coating with high hardness, characterized in that The nitrogen-saturated AlNbTiZrN wear-resistant coating with high hardness is formed by magnetron sputtering deposition of AlNbTiZr target material, and the nitrogen-saturated AlNbTiZrN wear-resistant coating is composed of Al, Nb, Ti, Zr and N elements, and the atomic percentage content of each element is: Al: 18.00at%~34.00at%, Nb: 12.00at%~27.00at%, Ti: 10.90at%~13.48at%, Zr: 10.94at%~25.52at%, N: 32.16at%~48.16at%.
2. The method for preparing the nitrogen-saturated AlNbTiZrN wear-resistant coating with high hardness as claimed in claim 1, characterized in that The preparation method is achieved by the following steps: S1. Substrate processing: The substrate is ultrasonically cleaned by using ethanol or acetone, and dried to obtain a cleaned substrate; S2. Film loading: The cleaned substrate is mounted on a rotating fixture, sent into a vacuum chamber of a magnetron sputtering device, and evacuated; S3, heating: Heat the vacuum chamber to 200-205°C and evacuate the chamber again; S4. Substrate cleaning: Argon gas is introduced into the vacuum chamber to perform plasma cleaning on the substrate; S5. Coating pre-deposition: Using AlNbTiZr alloy as the target material, increase the argon flow rate to 100-140 sccm, control the deposition gas pressure to 0.8-1.5 Pa, set the voltage of the bias power supply to 100-200 V, turn on the bias power supply, then turn on the DC pulse power supply, and perform pre-deposition for 2-5 minutes; S6. Coating deposition: After the pre-deposition is completed, the DC pulse power supply is kept on, the argon flow rate is gradually reduced, the nitrogen flow rate is increased, the argon flow rate is controlled to be 110-120 sccm, the nitrogen flow rate is controlled to be 3-6 sccm, the deposition pressure is maintained at 0.8-1.5 Pa, and vapor deposition is performed; S7. Cooling: After the temperature of the vacuum chamber is gradually cooled to room temperature and the atmosphere is vented, the substrate is taken out and a nitrogen-saturated AlNbTiZrN wear-resistant coating with high hardness is deposited on the substrate.
3. The method for preparing the nitrogen-saturated AlNbTiZrN wear-resistant coating with high hardness according to claim 2, characterized in that In step S1, the material of the substrate is a single metal, ceramic or alloy material.
4. The method for preparing the nitrogen-saturated AlNbTiZrN wear-resistant coating with high hardness according to claim 2, characterized in that In step S3, the vacuum is again evacuated to 3×10 -3 Pa.
5. The method for preparing the nitrogen-saturated AlNbTiZrN wear-resistant coating with high hardness according to claim 2, characterized in that The plasma cleaning process in step S4 is as follows: Introduce argon gas into the vacuum chamber and control the argon gas flow rate to 17 sccm. First turn on the ion source power supply and use the ion source to clean the substrate surface for 10 to 20 minutes. Then turn off the ion source power supply, turn on the bias power supply, and use the bias to clean for 10 to 20 minutes.
6. The method for preparing the nitrogen-saturated AlNbTiZrN wear-resistant coating with high hardness according to claim 5, characterized in that The ion source power supply parameters were set as follows: current 0.3 A, duty cycle 70%.
7. The method for preparing the nitrogen-saturated AlNbTiZrN wear-resistant coating with high hardness according to claim 5, characterized in that Set the bias power supply parameters as follows: voltage is 800V, duty cycle is 50%.
8. The method for preparing the nitrogen-saturated AlNbTiZrN wear-resistant coating with high hardness according to claim 2, characterized in that In step S5, the parameters of the DC pulse power supply are controlled as follows: power is 800-1200W, and duty cycle is 70%.
9. The method for preparing the nitrogen-saturated AlNbTiZrN wear-resistant coating with high hardness according to claim 2, characterized in that In step S6, the argon flow rate is controlled to be 100-105 sccm, the nitrogen flow rate is controlled to be 15-20 sccm, and the deposition pressure is maintained at 1.0 Pa to perform vapor deposition.
10. The method for preparing the nitrogen-saturated AlNbTiZrN wear-resistant coating with high hardness according to claim 2, characterized in that The thickness of the nitrogen-saturated AlNbTiZrN wear-resistant coating with high hardness in step S7 is 2.5-6.0 μm.
Citation Information
Patent Citations
High-hardness and high-elasticity-modulus multi-component nitride coating and preparation method thereof
CN106835037A
High-hardness and high-corrosion-resistance high-entropy alloy nitride coating and preparation method thereof
CN108220880A
Corrosion-resistant high-entropy alloy nitride coating, and preparation method and application thereof
CN111074224A
Method for manufacturing superhard high-entropy alloy nitride coating on alloy cutter
CN111560582A
High-entropy nitride anti-erosion coating as well as preparation method and device thereof
CN116005109A